Comparative Study of Equivalent Manning Roughness Coefficient for Channel with Composite Roughness - Ruslan Djajadi (Civil Engineering Dimension, 2009)
This paper reviews the applicability of nine selected expressions in determining the equivalent value of the Manning coefficient of roughness. For this purpose, a prismatic 4m-long and 0.05m-wide trapezoidal-shape channel was constructed, namely the homogeneous channel and the composite channel. The homogeneous channel had the same surface lining, whereas the composite channel had two different surface linings. Four different lining materials were considered: plaster, small, medium, and large-sized aggregates. The homogeneous channel showed a reliable Manning coefficient prediction, provided that a uniform flow was achieved. The roughness of the composite channel can be predicted accurately by the nine expressions; the average was 0.96, with standard deviation of 11.13%. Out of the nine expressions, the expression that considers wet-perimeter as its main parameter showed the best estimate. The error was about 2% with standard deviation of 5.15%. This can be actually traced back to the limited width of the test channel, thereby increasing the role of wet perimeter.